Teaching Phonemic Awareness in Multilingual Contexts: A Comparative Study of Filipino and Indonesian Students - Ocampo, Darrel M.; Marsella, Elisabeth (Program Studi Pendidikan Bahasa Inggris, 2025)
This study explores the challenges of teaching phonemic awareness among elementary students in multilingual settings, focusing on Filipino and Indonesian contexts. Given the linguistic diversity in both countries, the research investigates how native language interference, resource availability, and instructional strategies affect phonemic recognition and pronunciation accuracy. An exploratory sequential mixed-methods design was employed, combining quantitative assessments from 200 students (100 Filipino and 100 Indonesian) with qualitative insights from interviews involving 20 teachers. Quantitative findings revealed statistically significant differences in phonemic awareness performance, with Indonesian students outperforming their Filipino counterparts, likely due to more standardized language policies. Qualitative data highlighted persistent difficulties stemming from phonetic interference and inconsistent curricular support. The study underscores the need for culturally responsive teaching approaches and localized phonemic instruction tailored to students’ linguistic backgrounds. It is recommended that teacher training programs and educational policies be revised to integrate multilingual perspectives and improve phonemic instruction in diverse classrooms.